Development of an Equivalent Force Method and an Application in Simulating the Radiated Noise from an Operating Diesel Engine - Nickolas Vlahopoulos; Yury Kalish; S.T. Raveendra (Shock and Vibration)
In this paper a new methodology is presented for applying measured accelerations and forces as excitation on a structural finite element model in order to perform a forced frequency response analysis. The computed vibration constitutes the excitation for an acoustic boundary element analysis. The new developments presented in this paper are associated with: the equivalent force method that can prescribe the acceleration at certain parts of the structure; the integration within a single process of test data that define the excitation, with the vibration analysis, and the acoustic prediction; the utilization of the new technology in simulating the noise radiated from a running engine and determining the effects of design changes. Numerical results for noise radiated from a running engine are compared to test data for a baseline design. The effect of two structural design modifications on the radiated noise is computed, and conclusions are deduced.